5G explained : security and deployment of advanced mobile communications - Penttinen, Jyrki T. J. (Hoboken, NJ, USA : John Wiley & Sons, Inc., 2019)
Practical Guide Provides Students and Industry Professionals with Latest Information on 5G Mobile Networks Continuing the tradition established in his previous publications, Jyrki Penttinen offers 5G Explained as a thorough yet concise introduction to recent advancements and growing trends in mobile telecommunications. In this case, Penttinen focuses on the development and employment of 5G mobile networks and, more specifically, the challenges inherent in adjusting to new global standardization requirements and in maintaining a high level of security even as mobile technology expands to new horizons. The text discusses, for example, the Internet of Things (IoT) and how to keep networks reliable and secure when they are constantly accessed by many different devices with varying levels of user involvement and competence. 5G Explained is primarily designed for specialists who need rapid acclimation to the possibilities and concerns presented by 5G adoption. Therefore, it assumes some prior knowledge of mobile communications. However, earlier chapters are structured so that even relative newcomers will gain useful information. Other notable features include: -Three modules each consisting of three chapters: Introduction, Technical Network Description and Planning of Security and Deployment -Comprehensive coverage of topics such as technical requirements for 5G, network architecture, radio and core networks and services/applications -Discussion of specific security techniques in addition to common-sense guidelines for planning, deploying, managing and optimizing 5G networks 5G Explained offers crucial updates for anyone involved in designing, deploying or working with 5G networks. It should prove a valuable guide for operators, equipment manufacturers and other professionals in mobile equipment engineering and security, network planning and optimization, and mobile application development, or anyone looking to break into these fields.
10.4 Core and Radio Network Deployment Scenarios10.5 Standalone and Non-Standalone Deployment Scenarios; 10.6 5G Network Interfaces and Elements; 10.7 Core Deployment; 10.8 CoMP; 10.9 Measurements; References; Index; End User License Agreement
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 15, 2019).
Keywords: Global system for mobile communications -- Security measures; Global system for mobile communications -- Technological innovation; TECHNOLOGY & ENGINEERING / Mechanical; Electronic books; Electronic books